Macowanites ammophilus (Russalales) a new combination based on new evidence - Vidal i Frigola, Josep Maria; Calonge, Francisco de Diego; Martín Esteban, María Paz (Revista Catalana de Micologia, 2007)
Macowanites ammophilus (Russulales) a new combination based on new evidence. After studying abundant new collections, Gymnomyces ammophilus is transferred to the genus Macowanites based on the emergence of new data on morphological and genetic characters. A redescription of this taxon is given.